PENGARUH PERCIEVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI: (Studi Pada CV. Harmoni Bali Zoo) - I Kadek Wira Diana; I Gusti Bagus Honor Satrya (CV. Denasya Smart Publisher, 2024)
This research aims to analyze the effect of perceived organizational support on organizational commitment with job satisfaction as mediation (study at CV. Harmoni Bali Zoo). This research used a sample of 75 employees. The method used in this research is a non probability sampling method with questionnaire and interview techniques with PLS-based Structural Equation Modeling (SEM) inferential statistical analysis tools. The research results show that perceived organizational support has a positive and significant effect on organizational commitment. perceived organizational support has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational commitment, and job satisfaction mediates the effect of perceived organizational support on organizational commitment. The implication of this research is to prove three component theory and its relationship to the research variables. This research also offers the benefits of perceived organizational support, managing job satisfaction on organizational commitment.